Evaluation of the prevalence of musculoskeletal dysfunctions in blind veterans in Iran - V. nejati; R. Amini; M. Soroush; M. masoumi; A. Asadi (Afarand Scholarly Publishing Institute, 2009)
Introduction: The blindness makes specific kind of locomotion with characteristic bending of body, stepping gate and short steps. These changes in blind locomotion originate stress on musculo skeletal tissue and different musculo skeletal dysfunctions. Aim: The aim of these study is determining the epidemiology of musculo skeletal pain in blind veterans. Material and methods: in this cross sectional study we have collected data by questionnaire and have examined from all of 385 blind veteran who have participated in therapeutic and sportive camp of Iranian blinds veterans. (Mashhad, Iran 2005) Result: this study show high prevalence of musculo skeletal pain in blind veterans. Other finding of our study was high prevalence of postural deformities in blind veterans. Conclusion: according to the result, the prevalence of musculo skeletal pain in blinds veteran is more than normal population and they should be educated and treated for prevention, care and treatment of musculo skeletal pain.